HUBUNGAN MOTIVASI KERJA DENGAN KINERJA PERAWAT DI RUMAH SAKIT UMUM ROYAL PRIMA MEDAN TAHUN 2017 - Chiuman, Linda (Jurnal Keperawatan Priority, 2019)
Nursing services in hospital healthcare service is one of the crucial factors in defining the image and quality of a hospital. Nurse, a profession which has the highest amount of interaction with the patients and their family, is one of the core elements in determining the quality of healthcare service of a hospital. The purpose of this research is to discover the relation between internal as well as external motivations and the work related performance of the nurses, particularly those who are stationed at the wards in Royal Prima General Hospital Medan. The methodology used analytical study on the survey with cross-sectional approach. The respondents of the survey are all of the nurses who are stationed at the wards with total number of 168 respondents and the sampling method uses proportional random sampling method towards 110 respondents. The data obtained is analyzed with univariate, bivariate methods utilizing chi square as well as multivariate method utilizing double logistic binary regression test analysis with 5% of confidence interval.The outcome of the research shown that there are relations between internal as well as external motivations and work related performance of the nurses. Nurses with higher value of internal motivations have the chance of 3.061 times to perform better than those with lower value of internal motivations. Additionally, nurses with higher value of external motivations have the chance of 2.761 times to perform better than those with lower value of external motivations. Hence, it is much recommended to the hospital management boards to pay more attention towards the performance of the nurses by considering of giving incentives and rewards to the nurses based on their achievements and loyalty.